Y a-t-il analogie entre les opérations sous-jacentes aux constructions V ØNs et VPA ? - Sophie Dufossé-Sournin (Anglophonia)
The question here is to know whether the structure V ØNs (he was taking Ønotes) corresponds with the traditional scheme V + C1 or whether it can be compared with a phrasal verb (go up). Such a problem means calculating the constitutive properties of N and V from an enunciative point of view, studying minimal pairs of dependent elements and their influence on each other. A detailed analysis will show many similarities between V ØNs and VPA and its limitations as well.